MWQOJYNWQA's user avatar
MWQOJYNWQA's user avatar
MWQOJYNWQA's user avatar
MWQOJYNWQA
  • Member for 11 months
  • Last seen more than a month ago
Stats
550
reputation
7k
reached
3
answers
5
questions
Loading…
About

Let a = b

            a = b    
           a² = ab
      a² - b² = ab - b²
   (a+b)(a-b) = b(a-b)
        a + b = b

Since a=b,

        b + b = b
           2b = 1b
            2 = 1
This user doesn’t have any gold badges yet.
This user doesn’t have any silver badges yet.
14
bronze badges
19
Score
3
Posts
38
Posts %
19
Score
1
Posts
12
Posts %
19
Score
1
Posts
12
Posts %
3
Score
2
Posts
25
Posts %
3
Score
1
Posts
12
Posts %
3
Score
1
Posts
12
Posts %
Top posts
question
4
Nov 1, 2023
question
3
Feb 28, 2023
answer
3
Oct 17, 2023
question
2
Nov 13, 2023
question
0
Oct 16, 2023